Analisis Faktor-Faktor yang Mempengaruhi Permintaan Sayuran Hidroponik (Studi Kasus : Analisa Agrokreasi Jl. Eka Rasmi Gg. Eka Rosa Kelurahan Gedung Johor Kecamatan Medan Johor Kota Medan Sumatera Utara - Masitah, Tina Herianty; Hakim, Mukti; Sagala, Ade Saputra (JURNAL AGROPLASMA, 2025)
Hydroponics is a method of growing plants without using soil as a growing medium. The word hydroponic consists of 'hydro' (water) and 'ponic' (work); therefore, hydroponics can be understood as agriculture that uses water as the growing medium. Agrokreasi Analysis is a place for cultivating hydroponic vegetable plants and a marketplace for buying and selling hydroponic vegetable plants located in Medan City. This research uses the case study method, which is research conducted by directly observing the field. The data sources in this study are in the form of primary data. Primary data is data obtained directly from the source by conducting direct interviews with consumers who buy hydroponic vegetables at Agrokreasi Analysis using a questionnaire that has been prepared in advance according to the research objectives and needs. The data collection technique was carried out through interviews, observation, and questionnaires. The independent variables used in this study are price, number of family members, and consumer income, while the dependent variable in this study is the demand for palm kernel sprouts. The sample in this study consisted of 30 palm oil farmers with a demand for hydroponic vegetables. The sampling technique used was accidental sampling, which involves determining the sample based on chance, that is, whoever happens to purchase hydroponic vegetables and coincidentally meets the researcher. The analysis results indicate that the price variable (X1) affects the demand for hydroponic vegetables (Y) with a significance value of 0.009 < 0.05. The variable of family size (X2) affects the demand for hydroponic vegetables (Y) with a significance value of 0.505 > 0.05. The variable of consumer income (X3) affects the demand for hydroponic vegetables (Y) with a significance value of 0.718 > 0.05. Simultaneously, the study results obtained a significance value of 0.001 < 0.05, which means that price (X1), family size (X2), and consumer income (X3) simultaneously have a significant effect on the demand for hydroponic vegetables (Y) in Analisa Agrokreasi.Keywords: demand, price, number of family members, consumer income